2003
DOI: 10.1124/jpet.102.044719
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Modulation of Intestinal CYP3A Metabolism by P-Glycoprotein: Studies Using the Rat Single-Pass Intestinal Perfusion Model

Abstract: P-Glycoprotein (P-gp) has been hypothesized to modulate intestinal drug metabolism by increasing the exposure of drug to intracellular CYP3A through repeated cycles of drug absorption and efflux. The rat single-pass intestinal perfusion model was used to study this interplay in vivo. N-Methyl piperazine-PhehomoPhe-vinylsulfone phenyl (K77), a peptidomimetic cysteine protease inhibitor (CYP3A/P-gp substrate), and midazolam (CYP3A substrate) were each perfused through a segment of rat ileum alone and with the P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 20 publications
9
101
2
1
Order By: Relevance
“…In this model, a known concentration of drug is perfused through a section of the jejunum with intact blood supply. Disappearance of drug from the perfusate is attributed to intestinal absorption (Cummins et al, 2003;Berggren et al, 2004). Anatomical and physiological parameters of the gastrointestinal tract dramatically affect the rate and extent of absorption of ingested compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, a known concentration of drug is perfused through a section of the jejunum with intact blood supply. Disappearance of drug from the perfusate is attributed to intestinal absorption (Cummins et al, 2003;Berggren et al, 2004). Anatomical and physiological parameters of the gastrointestinal tract dramatically affect the rate and extent of absorption of ingested compounds.…”
Section: Introductionmentioning
confidence: 99%
“…P-gp, MRP1, and MRP2 were upregulated, especially after stimulation of cells with either the protein kinase-A (PKA) inducer sodium butyrate or the protein kinase-C (PKC) inducer phorbol ester 12-O-tetradecanoylphorbol-13-acetate (PMA) . In an in vivo intestinal perfusion model, these investigators had also shown modulation of intestinal CYP3A metabolism by P-gp (Cummins, CL, 2003). This has led to the hypothesis that both drug-transporter and drug-metabolizing enzymes act as a coordinated barrier against xenobiotic agents.…”
Section: Drug Efflux-drug Metabolism Alliancementioning
confidence: 99%
“…Appropriate pharmacological testing in disease models are carried out to determine 50% effective dose (ED 50 ). For some anti-tumor and anti-viral agents, even IC 90 (90% inhibitory concentration) is incorporated in these initial studies in order to demonstrate the potency (Cummins CL, et al, 2003). Following acute administration, analytical methods are developed for determination of absorption, distribution, metabolism and excretion (ADME) of the drug.…”
Section: Importance Of Preclinical In Vivo Modelsmentioning
confidence: 99%
“…The bioavailability of an orally administered drug is primarily dependent on the transporters expressed on the apical/basolateral side of enterocytes that influence both the fraction of drug absorbed [52,53] and the fraction escaping gut metabolism. It is difficult to reproduce the complexity of the human gut within a laboratory setting; therefore, efforts are being made to incorporate drug absorption into PBPK models by taking into account several physiological elements of the gastro-intestinal tract, e.g., pH, active transporters, and metabolizing enzymes [54].…”
Section: Intestinal Transporters Linked To Ivive-pbpk Model For Oral mentioning
confidence: 99%